La ecografía intraoperatoria en cirugía hepática: Comunicación preliminar - Torterolo, Edgardo; Kaitazzof, Pedro; Fernández, William (Cirugía del Uruguay, 1994)
lntraoperative echography is an advance in hepatic surgery. The authors state their group's experience, pointing out the importance of segmentary localization of hepatic tumours and their vascular and biliar relations. This anatomical survey makes possible the evaluation of resection extension. In the case of methastases, they emphasize the importance of mapping and evaluation of vascular extension in order to determine resectability. Another advance is the possibility of colouring segments in order to obtain a more anatomical resection.